2017
DOI: 10.1212/wnl.0000000000003882
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacotherapy for diabetic peripheral neuropathy pain and quality of life

Abstract: For reducing pain, duloxetine and venlafaxine, pregabalin and oxcarbazepine, tricyclic antidepressants, atypical opioids, and botulinum toxin were more effective than placebo. However, quality of life was poorly reported, studies were short-term, drugs had substantial dropout rates, and opioids have significant risks. Future studies should evaluate longer-term outcomes, use methods and measures recommended by pain organizations, and assess patients' quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(106 citation statements)
references
References 38 publications
1
99
0
6
Order By: Relevance
“…Studies were however short term and drugs had substantial discontinuation rates of~10%. 96 The limited benefit of any one agent alone reflects the complex etiologic basis of neuropathic pain. Thus, there is an increasing recognition that "one size does not fit all," and rather than having an agnostic approach (ie, blindly trying different therapies until one works), we should consider better clinical phenotyping and targeted therapies.…”
Section: Symptomatic Treatment Of Dpnmentioning
confidence: 99%
“…Studies were however short term and drugs had substantial discontinuation rates of~10%. 96 The limited benefit of any one agent alone reflects the complex etiologic basis of neuropathic pain. Thus, there is an increasing recognition that "one size does not fit all," and rather than having an agnostic approach (ie, blindly trying different therapies until one works), we should consider better clinical phenotyping and targeted therapies.…”
Section: Symptomatic Treatment Of Dpnmentioning
confidence: 99%
“…Smith and his colleagues reported that treatment for pain intensity only did not result in any improvement of the QoL of patients with trigeminal nerve injuries (Smith et al, ). A recently published systematic review on the effect of pharmacotherapy for diabetic peripheral neuropathy pain and quality of life stated that contrary to the significant analgesic effect of duloxetine, venlafaxine and other analgesics, QoL was poorly reported because few studies reported this value (only when the results were significant) or the results were inconsistent (Waldfogel et al, ). As a result, it may be inappropriate to consider the effect of analgesics and alleviation of pain intensity only when we are trying to treat the complexed NeP and improve QoL of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Hempe et al [59] evaluated if nephropathy and neuropathy in ZDF rats are linked to the hyperglycemic state of the rats and are real diabetic late complications or are related to other characteristics of the fa/fa genotype. Good glycemic control may be effective in delaying the neuropathic symptoms in diabetic patients [66].…”
Section: Zucker Diabetic Fatty Ratsmentioning
confidence: 99%